İNFLAMATUVAR BARSAK HASTALIĞI TANILI HASTALARDA ADALİMUMAB VE İNFLİKSİMAB TEDAVİSİNE YANITIN RETROSPEKTİF OLARAK DEĞERLENDİRİLMESİ - BULU, AYKUT (Fırat Üniveristesi, 2020)
Ülseratif kolit ve Crohn hastalığı inflamatuvar barsak hastalığının majör iki formudur. Crohn hastalığının klinik şiddetini belirlemek için Crohn hastalığı aktivite indeksi kullanılır. Ülseratif kolitin klinik şiddetini belirlemek için Truelove-wittz aktivite indeksi kullanılır. Adalimumab ve infliksimab inflamatuvar barsak hastalığı olan hastalarda tedavide kullanılan biyolojik ajanlardır. Bu çalışmanın amacı inflamatuvar barsak hastalığı olan hastalarda adalimumab ve infliksimab tedavisine yanıtın retrospektif değerlendirilmesidir. Fırat Üniversitesi Hastanesi Gastroenteroloji polikliniklerinde ve kliniklerinde, Ocak 2008-Nisan 2019 tarihleri arasında takip edilmiş inflamatuvar barsak hastalığı tanısı olan, 18 yaş üzerindeki hastaların verileri incelemeye alındı. İncelenen hastalardan adalimumab ve infliksimab tedavisini en az 4 hafta düzenli olarak almış 80 hasta çalışmaya dahil edildi. Adalimumab ve infliksimab tedavisine yanıtı değerlendirme amacıyla hastalığın aktivitesiyle ilişkili parametreler olan lökosit, eritrosit sedimantasyon hızı, C-reaktif protein ve nötrofil/lenfosit oranı değerlerinin tedaviden önceki ile tedaviden sonraki değerleri kıyaslandı. Ayrıca bu hastaların tedaviden önceki ve sonraki hemoglobin düzeyleri karşılaştırıldı. Ülseratif kolit ve Crohn hastalığı aktivitesinin değerlendirilmesinde kullanılan eritrosit sedimantasyon hızı, C-reaktif protein, lökosit ve nötrofil/lenfosit oranı seviyeleri adalimumab ve infliksimab tedavisi sonrası tedavi öncesi seviyelere göre hastalarda anlamlı derecede düşüktü (p<0,05). Adalimumab ve infliksimab tedavisi almış ülseratif kolit ve Crohn hastalarının tedaviden sonra hemoglobin düzeylerinin tedavi öncesine göre anlamlı derecede yüksek olduğu izlendi (p<0,05). Adalimumab ve infliksimab tedavisi almış Crohn hastalarının Crohn hastalığı aktivite indeksleri kıyaslandı ve tedavi sonrasında tedavi öncesine göre anlamlı derecede düşük izlendi (p<0,05). Adalimumab ve infliksimab tedavisi almış Ülseratif kolit hastalarının Truelove-wittz Aktivite indeksleri kıyaslandı ve tedavi sonrasında tedavi öncesine göre anlamlı derecede düşük izlendi (p<0,05). Crohn hastalarının %83,3'ü, ülseratif kolit hastalarının %84,6'sı iyileşti. Adalimumab ve infliksimab tedavisi inflamatuvar barsak hastalığı olan hastalarda tedavide aktif hastalığın iyileşmesi üzerine etkili oldu. Adalimumab ve infliksimabın güvenilirliğinin yüksek olduğu fakat düşük oranda allerji, lenfadenopati ve lökopeni yan etkileri olduğu görüldü. Anahtar kelimeler: İnflamatuvar barsak hastalığı, crohn hastalığı aktivite indeksi, Truelove-wittz aktivite indeksi, adalimumab, infliksimab.

Inflammatory bowel disease encompasses two major forms, known as Crohn's disease and ulcerative colitis. The Crohn's Disease Activity Index is used to determine the severity of disease activity in patients with Crohn's disease. On the other hand, the Truelove-Witts activity index is used to determine the severity of disease activity in patients with ulcerative colitis. Adalimumab and infliximab are biological agents used in the treatment of patients with inflammatory bowel disease. The aim of this study is to conduct a retrospective evaluation regarding the response to adalimumab and infliximab treatment in patients with inflammatory bowel disease. The data of the patients who was over the age of 18, diagnosed with inflammatory bowel disease, and followed up in Gastroenterology Clinic and Outpatient Clinic of Firat University Hospital between January 2008-April 2019 were assessed. Eighty patients who received adalimumab and infliximab treatment regularly for at least 4 weeks were included in the study. Leukocyte, erythrocyte sedimentation rate, C-reactive protein and neutrophil / lymphocyte ratio, which are the parameters related to the activity of the disease, were compared prior to and after treatment in order to evaluate the response to adalimumab and infliximab treatment. Hemoglobin levels of the patients prior to and after treatment were also compared. Erythrocyte sedimentation rate, C-reactive protein, leukocyte and neutrophil / lymphocyte ratio levels; which was used in the evaluation of ulcerative colitis and Crohn's disease activity, were found significantly lower in patients after adalimumab and infliximab treatment when compared to pre-treatment levels (p <0.05). When the hemoglobin levels of the patients with ulcerative colitis and Crohn's disease were analyzed, it was found that patients who received adalimumab and infliximab treatment had significantly higher levels of hemoglobin after the treatment when compared to the hemoglobin levels prior to the treatment (p <0.05). Moreover, the Crohn's Disease Activity Index of patients who were diagnosed with Crohn's disease, and received adalimumab and infliximab treatment were compared, and it was found that it was significantly lower after the treatment (p <0.05). Truelove and Witts Activity Index of patients who were diagnosed with Crohn's disease, and received adalimumab and infliximab treatment were compared prior to and after the treatment, and it was found that it was significantly lower after the treatment (p <0.05). The results showed that the recovery rate was %83,3 in crohn's disease and %84,6 in ulcerative colitis patients. Adalimumab and infliximab treatment were effective on healing of active disease in patients with inflammatory bowel disease. It was also concluded that although the safety of adalimumab and infliximab was high, but few allergy, lymphadenopathy and leukopenia side effects were observed. Keywords: Inflammatory bowel disease, crohn disease activity index, Truelove-wittz activity index, adalimumab, infliximab
The retrospective evaluation of response to adalimumab and infliximab treatment in patients diagnosed with inflammatory bowel disease
Keywords: Gastroenteroloji